Serum Vitamin E Levels in Multiple Sclerosis: Association with Diagnosis, Cognitive Function, Disability, and Depressive Symptoms - Francesco Bruno; Patrizia Spadafora; Mario Luca Cuconati; Antonio Qualtieri; Ida Veltri; Selene De Benedittis; Beatrice Maria Greco; Annamaria Cerantonio; Luigi Citrigno; Gemma Di Palma; Olivier Gallo; Alberto Montesanto; et al. (Molecular Neurobiology, 2026)
Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease of the central nervous system and the most common neurodegenerative disease in young adults, characterized by motor, sensory, visual, and cognitive impairments. Vitamin E (α-Tocopherol), a fat-soluble antioxidant, may influence cognitive function, disability, and mood in MS. One hundred eighty-four Italian Caucasian MS patients and ninety-four healthy controls were included. Clinical and demographic variables were recorded, and serum vitamin E levels were measured by HPLC. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), disability with the Expanded Disability Status Scale (EDSS), and depressive symptoms with the Hamilton Depression Rating Scale (HDRS). Logistic and linear regression analyses were performed, adjusting for demographic, MS-related, and metabolic confounders. Bonferroni correction was applied. Discriminative ability for clinical cut-offs (MMSE ≤ 24, EDSS ≥ 6, HDRS ≥ 8) was assessed using receiver operating characteristic (ROC) curves. MS patients had significantly lower serum vitamin E levels compared to controls. Lower vitamin E levels were associated with MS diagnosis. In MS patients, higher vitamin E levels were associated with better cognitive performance and lower disability. All associations remained significant after Bonferroni correction in fully adjusted models. No significant relationship was found between vitamin E levels and depressive symptoms. Vitamin E showed good discriminative ability. Serum vitamin E levels showed significant associations with MS diagnosis, cognitive function, and disability, with good discriminative ability. Longitudinal studies are needed to clarify whether low vitamin E levels influence the risk of developing MS, while randomized controlled trials are warranted to determine whether vitamin E supplementation may provide clinical benefits.